Co-ingestion of protein or a protein hydrolysate with carbohydrate enhances anabolic signaling, but not glycogen resynthesis, following recovery from prolonged aerobic exercise in trained cyclists - Cogan, K. E.; Evans, M.; Iuliano, E.; Melvin, A.; Susta, D.; Neff, K.; de Vito, G.; Egan, B. (European Journal of Applied Physiology, 2018)
Purpose: The effect of carbohydrate (CHO), or CHO supplemented with either sodium caseinate protein (CHO-C) or a sodium caseinate protein hydrolysate (CHO-H) on the recovery of skeletal muscle glycogen and anabolic signaling following prolonged aerobic exercise was determined in trained male cyclists [n = 11, mean ± SEM age 28.8 ± 2.3 years; body mass (BM) 75.0 ± 2.3 kg; VO2peak 61.3 ± 1.6 ml/kg/min]. Methods: On three separate occasions, participants cycled for 2 h at ~ 70% VO2peak followed by a 4-h recovery period. Isoenergetic drinks were consumed at + 0 and + 2 h of recovery containing either (1) CHO (1.2 g/kg BM), (2) CHO-C, or (3) CHO-H (1.04 and 0.16 g/kg BM, respectively) in a randomized, double-blind, cross-over design. Muscle biopsies from the vastus lateralis were taken prior to commencement of each trial, and at + 0 and + 4 h of recovery for determination of skeletal muscle glycogen, and intracellular signaling associated with protein synthesis. Results: Despite an augmented insulin response following CHO-H ingestion, there was no significant difference in skeletal muscle glycogen resynthesis following recovery between trials. CHO-C and CHO-H co-ingestion significantly increased phospho-mTOR Ser2448 and 4EBP1 Thr37/46 versus CHO, with CHO-H displaying the greatest change in phospho-4EBP1 Thr37/46. Protein co-ingestion, compared to CHO alone, during recovery did not augment glycogen resynthesis. Conclusion: Supplementing CHO with intact sodium caseinate or an insulinotropic hydrolysate derivative augmented intracellular signaling associated with skeletal muscle protein synthesis following prolonged aerobic exercise.